Prolonged cognitive–motor impairments in children and adolescents with a history of concussion - Marc Dalecki; David Albines; Alison Macpherson; Lauren E Sergio (Concussion)
Aim: We investigated whether children and adolescents with concussion history show cognitive–motor integration (CMI) deficits. Method: Asymptomatic children and adolescents with concussion history (n = 50; mean 12.84 years) and no history (n = 49; mean: 11.63 years) slid a cursor to targets using their finger on a dual-touch-screen laptop; target location and motor action were not aligned in the CMI task. Results: Children and adolescents with concussion history showed prolonged CMI deficits, in that their performance did not match that of no history controls until nearly 2 years postevent. Conclusion: These CMI deficits may be due to disruptions in fronto-parietal networks, contributing to an increased vulnerability to further injury. Current return-to-play assessments that do not test CMI may not fully capture functional abilities postconcussion.